Sri Baduga Museum as a Source For Social Learning in The Material of People Existence in Hindu – Buddhism Period - Rosyana, Bunga (Universitas Pendidikan Indonesia, 2019)
This research is based on the social studies learning process that has been happening so far, limited by formal classrooms, educators only use textbooks as the only source of social studies learning, in order to achieve social studies learning objectives, it is necessary to choose learning resources that are in accordance with the material. Sri Baduga Museum is conceptually relevant to be used as a source of social studies learning in the subject of community life during the Hindu-Buddhist period. The purpose of this study is to find out the collections in the Sri Baduga museum that can support the material of community life during the Hindu-Buddha, to find out the activities which are conducted by students in utilizing Sri Baduga Museum collection that supports the subject of community life during the Hindu-Buddha period, to find out the optimization Sri Baduga Museum as a source of social studies learning in the subject of community life during the Hindu-Buddhist period, and to find out the obstacles of the use of Sri Baduga Museum as a source of social studies learning in the subject of community life during the Hindu-Buddhist period. Data collection will be conducted by observation, interviews and documentation. This study reveals that; First, there are collections that support the subject of community life in the Hindu-Buddhist period such as, replicas of Inscriptions, replicas of Arca, replicas of Candi. Second, the activities which are conducted by students are tour activities which is going around from the first floor to the third floor, watching movies, recording important things and taking photos as documentation. Third, optimization which are conducted by the staff are providing good facilities, as well as adding collections, revitalizing the Classic Period Room. Fourth, obstacles which are experienced in terms of funding.